Effectiveness of foreign development assistance in mitigating natural disasters' impact: Case study of Pacific island countries - Hong Chen; Baljeet Singh (Asian Development Bank Institute (ADBI), 2020)
Natural disasters bring tremendous destruction to small island economies in the South Pacific region. Foreign development aid, as an important source of green finance in the region, has the fundamental purpose of reducing natural disasters' effect on the small island economies. With country level data on 13 Pacific island countries over 1981-2014, this study assesses the effectiveness of foreign development assistance in mitigating natural disasters' impact on Pacific economic growth. With the application of panel integration tests and the system generalized method of moments estimator, this study provides non-spurious and consistent empirical estimation of a growth model. It is found that while natural disasters greatly hinder economic growth in the region, official development assistance significantly mitigates such adverse effects.
Keywords: Q54; O49; R10; F35; 330; natural disaster; economic growth; South Pacific region; foreign development assistance